СВЧ ферромагнитный резонанс в наночастицах NiFe2O4 - Кравчук, О. А.; Вакула, А. С.; Тарапов, С. И. (ХНУРЕ, 2018)
The comparison of high-frequency properties of NiFe2O4 nanoparticles synthesized by different methods is performed. Itisshown, thatthe heat treatment in argon at500 ° C leads to increasing the value of the total magnetic anisotropy field.
Keywords: Ферромагнитный резонанс; наночастицы